2012
DOI: 10.1371/journal.pone.0045152
|View full text |Cite
|
Sign up to set email alerts
|

SVMTriP: A Method to Predict Antigenic Epitopes Using Support Vector Machine to Integrate Tri-Peptide Similarity and Propensity

Abstract: Identifying protein surface regions preferentially recognizable by antibodies (antigenic epitopes) is at the heart of new immuno-diagnostic reagent discovery and vaccine design, and computational methods for antigenic epitope prediction provide crucial means to serve this purpose. Many linear B-cell epitope prediction methods were developed, such as BepiPred, ABCPred, AAP, BCPred, BayesB, BEOracle/BROracle, and BEST, towards this goal. However, effective immunological research demands more robust performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
202
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(214 citation statements)
references
References 29 publications
(31 reference statements)
1
202
0
1
Order By: Relevance
“…SVMTriP achieves a sensitivity of 80.1% and a precision of 55.2% and the AUC value 0.702, when tested on nonredundant epitopes extracted from IEDB [78]. A comparative study concluded that the methods based on sequence analysis do not predict epitopes better than chance.…”
Section: In Silico B-cell Epitope Predictionmentioning
confidence: 99%
“…SVMTriP achieves a sensitivity of 80.1% and a precision of 55.2% and the AUC value 0.702, when tested on nonredundant epitopes extracted from IEDB [78]. A comparative study concluded that the methods based on sequence analysis do not predict epitopes better than chance.…”
Section: In Silico B-cell Epitope Predictionmentioning
confidence: 99%
“…The proteins that are localized on cell surface were analyzed, for antigenic property by Vaxijen 2.0 [27], presence of transmembrane helices by TMHMM [28], identifying the domains that have the capability to bind to immune cells of humans by domain search against InterProScan [29], and finally characterizing the vaccine candidate by identifying the epitopes by SVMTriP [30]. Then, broad spectrum analysis and non-human gut flora analysis were carried out for drug target and vaccine candidate by BLASTP option from Human Microbiome Project [31,32].…”
Section: Data Collection Databases and Tools Employedmentioning
confidence: 99%
“…BcpredB-cell epitope prediction (EL-Manzalawy et al 2008) server uses Artificial Intelligence Research Laboratory at http://ailab.cs.iastate.edu/bcpreds/index.html. Svmtrip (Yao et al 2012) at http://sysbio.unl.edu/SVMTriP/prediction.php predicts antigenic epitope within sequence input. In this method, Support Vector Machine (SVM) has been used by combining the Tri-peptide similarity and Propensity scores (SVMTriP) in order to achieve the higher accuracy and specificity by leave-one-out test.…”
Section: Sequence-based B Cell Epitope Predictionmentioning
confidence: 99%